2008
DOI: 10.1007/s10522-008-9196-9
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil protects ATP-sensitive potassium channels against oxidation-induced dysfunction in cardiomyocytes of aging rats

Abstract: ATP-sensitive potassium channels (K(ATP) channels) regulate vascular tone and cardiac contraction through their action on the membrane potential of smooth muscle cells and cardiomyocytes. Because aging and diseases alter K(ATP) channel activity, many pharmacological treatments aimed at improving their function, therefore cardiovascular function, have been evaluated. Nicorandil, a K(ATP) channel opener, nitric oxide donor and antioxidant, is used as a treatment of angina pectoris and induces vasodilation, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
(53 reference statements)
0
11
0
1
Order By: Relevance
“…In addition to the robust cardioprotection derived from direct targeting of mitochondria to modulate electron transport in the present study, mitochondria from aged hearts remain responsive to direct manipulation of the K ATP channel by nicorandil 46 or diazoxide treatment. 47 Direct modulation of permeability transition pore susceptibility 4850 also limits damage in the aged heart.…”
Section: Discussionmentioning
confidence: 72%
“…In addition to the robust cardioprotection derived from direct targeting of mitochondria to modulate electron transport in the present study, mitochondria from aged hearts remain responsive to direct manipulation of the K ATP channel by nicorandil 46 or diazoxide treatment. 47 Direct modulation of permeability transition pore susceptibility 4850 also limits damage in the aged heart.…”
Section: Discussionmentioning
confidence: 72%
“…However, cardiac fibroblasts pretreated with nicorandil (3 mol/l, 30 min) had significantly decreased levels of Ang-II-induced ERK phosphorylation. Studies on the antioxidative effect of nicorandil in inhibiting radical production revealed that it possesses a certain degree of protective effects in vitro [13,21,22] and in vivo [23] . The protective characteristics may be associated with their antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased intracellular Ca2+ for a prolonged period causes increased Ca2+ uptake by mitochondria, which further leads to mitochondrial dysfunction and cardiomyocyte death. Similarly, expression and/or function of ATP sensitive K+ (KATP) channels decreases with advanced age affecting the electrical activities of cardiomyocytes [47][49]. Decreased KATP channel density represents a possible mechanism for decreased tolerance of aged heart against ischemic injury [47],[48].…”
Section: Aging and The Heartmentioning
confidence: 99%